Is inertial training more effective than traditional resistance training in young healthy males? - Naczk, Alicja; Kisiel-Sajewicz, Katarzyna; Gajewska, Ewa; Gramza, Piotr; Jędzrzejczak, Tomasz; Naczk, Mariusz (Frontiers in Physiology, 2024)
ObjectivesInertial training, also called flywheel training is more and more popular among sportsmen. The available data concerning the effectiveness of inertial training compared to conventional resistance strength training are contradictory. The aim of this study was to compare the impact of inertial training (IT) vs. traditional gravity-dependent resistance training (TRT) on elbow flexor and knee extensor strength.MethodsTwenty-six young, recreationally active males were randomized into IT group (n = 13) or TRT group (n = 13). Both groups performed strength training three times a week for 6 weeks. Before and after training, the maximum force of the trained muscles was evaluated under training conditions (one repetition maximum under gravity-dependent conditions and maximal force under inertial conditions) and isometric conditions. Countermovement jump, squat jump, pull-up test, and limb circumference were also evaluated.ResultsElbow flexor muscle strength and arm circumference increased significantly in both IT and TRT over the course of training. There were no significant differences in relative muscle strength increases between groups. Knee extensor muscle strength also improved significantly in IT, regardless of the tested conditions, while TRT showed significant changes in one repetition maximum and isometric force but no significant changes in force obtained under inertial conditions. Thigh circumference increased in IT (P ≤ 0.05) but was unchanged in TRT. Jumping abilities improved significantly in both groups, without any differences between groups.ConclusionWe cannot confirm the superiority of inertial training over traditional resistance training definitively. Nevertheless, inertial training had a slight advantage over traditional resistance training when knee extensor muscle training was considered.